Affection in a Moral Coexistence from the perspective of the Quran karim - Hassan Seyed Pour Azar (اخلاق وحیانی)
Theological instructor and MA in Theoretical Principles of Islam (seyed_porazar@yahoo.com) Social life is a necessity for mankind and his felicity depends on his manner of social coexistence, thus, one cannot be indifferent about the manner in which to coexist with others and to live with others in just any way. Yet, the question is raised here that what is the best way in which the felicity of the majority of mankind is achieved, and what is the most important characteristic that would guarantee a felicitous coexistence of human beings? The method that is presented to mankind by the Quran is a moral coexistence. The Quran calls the people to observe the ethical values in their coexistence so that it would lead to the training of the members of the society and the synergy of moral virtues. In this method of coexistence, the peacefulness of the social interactions is not the most important point; rather, the most important principle here is the moral excellence of the members of the society. The most important factor for training and the establishment of moral values is affection, for affection creates a sense of sympathy among the members of the society and molds the society into a single body. What is meant here by affection is the kind of sentiment that would decrease social vices and would increase virtues and it is a kind of affection that is called the “affection in the cause of Allah” and the “affection for Allah”. In other words, it is a benevolent affection which originates from man’s affection for the absolute goodness, i.e. Allah Almighty. Moreover, since the purpose of such affection is to pave the way for moral training, it takes various forms to fit various circumstances and different social groups; thus, it sometimes takes the form of adherence and approval, and other times, it realizes in the form of disapproval, just as the affection of a doctor causes him to disapprove of and hate the sickness in the body of his patients. Based on the teachings of the Quran, the affection of the Prophet of Islam (may Allah bless him and his descendants) for the people, the affection of the believers for each other, and even the affection of the believers for unbelievers and enemies in different forms, all lead to the synergy of moral virtues. Similarly, the disapproval and enmity of the believers towards those unbelievers who insist on their enmity with the believers is also a manifestation of Divine Mercy which causes them to exit the authority of Satan and accept the authority of Allah Almighty. The prosperity of affection in coexistence is achieved through gentleness and tenderness of social behavior, being benevolent to the public, patience in the face of adversities and trusting Allah’s power and might.